2014
DOI: 10.4187/respcare.03200
|View full text |Cite
|
Sign up to set email alerts
|

Asthma and Adherence to Inhaled Corticosteroids: Current Status and Future Perspectives

Abstract: Inhaled corticosteroids (ICS) are the cornerstone of maintenance asthma therapy. However, in spite of this, adherence to ICS remains low. The aim of this systematic literature review was to provide an overview of the current knowledge of adherence to ICS, effects of poor adherence, and means to improve adherence. A total of 19 studies met the inclusion criteria: 9 focusing on the level of adherence, 6 focusing on effects of poor adherence, and 7 focusing on interventions to improve adherence. Three of the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
189
2
5

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(210 citation statements)
references
References 66 publications
10
189
2
5
Order By: Relevance
“…Poor adherence in asthma is well-documented [29,30], even in difficult asthma: A study of adults referred to a clinic for difficult asthma revealed that 35% of the patients filled their ICS prescriptions less than 50% of the time [31]. Poor adherence with controller medication is associated with poor disease control, and it is estimated that 24% of exacerbations and 60% of asthma-related hospital admissions may be attributed to poor adherence [29,32].…”
Section: Systematic Assessment Of Severe Asthmamentioning
confidence: 99%
See 1 more Smart Citation
“…Poor adherence in asthma is well-documented [29,30], even in difficult asthma: A study of adults referred to a clinic for difficult asthma revealed that 35% of the patients filled their ICS prescriptions less than 50% of the time [31]. Poor adherence with controller medication is associated with poor disease control, and it is estimated that 24% of exacerbations and 60% of asthma-related hospital admissions may be attributed to poor adherence [29,32].…”
Section: Systematic Assessment Of Severe Asthmamentioning
confidence: 99%
“…Poor adherence with controller medication is associated with poor disease control, and it is estimated that 24% of exacerbations and 60% of asthma-related hospital admissions may be attributed to poor adherence [29,32]. …”
Section: Systematic Assessment Of Severe Asthmamentioning
confidence: 99%
“…после выписки из стационара [29]. И хорошо известно, что низкая приверженность приводит к недо-статочно эффективному воздействию на воспаление, лежащее в основе заболевания, к повышенному риску обострений и риску летального исхода [30,[31][32][33][34][35][36]. Кроме того, чрезмерное использование монотерапии короткодействующими бета2-агонистами (КДБА) как единственно возможной симптоматической терапии при легкой астме приводит к тому, что регулярная тера-пия ИКС назначается с запозданием [37] и пациент достаточно долго не принимает никакой противовос-палительной терапии.…”
Section: низкая приверженность регулярной терапии иксunclassified
“…The incidence of the disease is increasing at an alarming rate affecting 1 in 10 children and 1 in 12 adults with a total of 300 million worldwide [5]. Worldwide, deaths from asthma have reached over 250,000 annually.…”
Section: Editorialmentioning
confidence: 99%